Reframing How Physical Activity Reduces The Incidence of Clinically-Diagnosed Cancers: Appraising Exercise-Induced Immuno-Modulation As An Integral Mechanism - Emery, Annabelle; Moore, Sally; Turner, James E.; Campbell, John P. (Frontiers in Oncology, 2022)
Undertaking a high volume of physical activity is associated with reduced risk of a broad range of clinically diagnosed cancers. These findings, which imply that physical activity induces physiological changes that avert or suppress neoplastic activity, are supported by preclinical intervention studies in rodents demonstrating that structured regular exercise commonly represses tumour growth. In Part 1 of this review, we summarise epidemiology and preclinical evidence linking physical activity or regular structured exercise with reduced cancer risk or tumour growth. Despite abundant evidence that physical activity commonly exerts anti-cancer effects, the mechanism(s)-of-action responsible for these beneficial outcomes is undefined and remains subject to ongoing speculation. In Part 2, we outline why altered immune regulation from physical activity - specifically to T cells - is likely an integral mechanism. We do this by first explaining how physical activity appears to modulate the cancer immunoediting process. In doing so, we highlight that augmented elimination of immunogenic cancer cells predominantly leads to the containment of cancers in a ‘precancerous’ or ‘covert’ equilibrium state, thus reducing the incidence of clinically diagnosed cancers among physically active individuals. In seeking to understand how physical activity might augment T cell function to avert cancer outgrowth, in Part 3 we appraise how physical activity affects the determinants of a successful T cell response against immunogenic cancer cells. Using the cancer immunogram as a basis for this evaluation, we assess the effects of physical activity on: (i) general T cell status in blood, (ii) T cell infiltration to tissues, (iii) presence of immune checkpoints associated with T cell exhaustion and anergy, (iv) presence of inflammatory inhibitors of T cells and (v) presence of metabolic inhibitors of T cells. The extent to which physical activity alters these determinants to reduce the risk of clinically diagnosed cancers – and whether physical activity changes these determinants in an interconnected or unrelated manner – is unresolved. Accordingly, we analyse how physical activity might alter each determinant, and we show how these changes may interconnect to explain how physical activity alters T cell regulation to prevent cancer outgrowth.